BRCA1/2 gene mutations do not affect the capacity of oocytes from breast cancer candidates for fertility preservation to mature in vitro. Issue 2 (17th December 2018) - Grynberg, Michaël; Dagher Hayeck, Bénédicte; Papanikolaou, Evangelos G; Sifer, Christophe; Sermondade, Nathalie; Sonigo, Charlotte
Abstract: STUDY QUESTION: Are the maturation rates of oocytes recovered from small antral follicles different between breast cancer patients presenting with or without a BRCA 1/2 gene mutation? SUMMARY ANSWER: BRCA 1 / 2 gene mutations do not affect the capacity of oocytes from breast cancer candidates for fertility preservation to mature in vitro . WHAT IS KNOWN ALREADY: Mutations in the BRCA1 and BRCA2 genes are associated with an increased risk for developing breast and ovarian cancer. Controversy exists about fertility and ovarian reserve in BRCA mutation carriers. Studies suggest that these patients may have low ovarian reserve and poor response to ovarian stimulation. The impaired ability of the mutated BRCA gene to repair double-strand breaks in DNA may prompt oocyte aging, apoptosis and meiotic errors. IVM of oocytes retrieved at germinal vesicle stage, followed by vitrification of metaphase II (MII) oocytes has recently emerged as an option for young women seeking fertility preservation, when ovarian stimulation is unfeasible. STUDY DESIGN, SIZE, DURATION: Retrospective cohort study involving 329 breast cancer candidates for fertility preservation using IVM between January 2014 and December 2017. PARTICIPANTS/MATERIALS, SETTING, METHODS: Inclusion criteria were: age 18–40 years; two ovaries present; no history of chemotherapy; test for BRCA 1/2 mutations performed. Before immature oocyte retrieval, all follicles measuring 2–9 mm in diameter were precisely counted on both ovaries and serum anti-Müllerian hormone (AMH) was measured irrespective of the phase of the cycle. Number of cumulus oocyte complexes (COC) retrieved, maturation rate and number of MII oocytes cryopreserved were compared according to BRCA mutation status. MAIN RESULTS AND THE ROLE OF CHANCE: Overall, BRCA-mutated women ( n = 52) and BRCA-negative women ( n = 277) were comparable in terms of age (31.7 ± 3.9 versus 32.3 ± 3.8 years, respectively, P = 0.3), BMI (23.4 ± 4.7 versus 22.6 ± 3.7 kg/m 2, respectively, P = 0.3) and ovarian reserve tests (antral follicle count: 20.5 ± 11.4 versus 21.7 ± 12.1 follicles, P = 0.5; serum AMH levels: 3.6 ± 2.9 versus 4.1 ± 3.6 ng/ml, P = 0.3, respectively). The number of COCs retrieved did not differ significantly between both groups (8.9 ± 6.9 versus 9.9 ± 8.1 oocytes, P = 0.5). After similar IVM rates (67 ± 24 versus 62 ± 23%, P = 0.2), the number of MII oocytes cryopreserved was similar in patients presenting BRCA mutation or not (5.1 ± 3.8 versus 6.1 ± 5.1, P = 0.1, respectively). LIMITATIONS, REASONS FOR CAUTION: Given the low incidence of the mutation, these preliminary findings should be confirmed by further multi-center studies. WIDER IMPLICATIONS OF THE FINDINGS: Although BRCA mutations are known to alter DNA repair mechanism, it does not seem to impair oocyte capacity to mature in vitro . STUDY FUNDING/COMPETING INTEREST(s): None.